2016
DOI: 10.1002/pbc.26259
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of protocadherin 17 and its prognostic value in pediatric acute lymphoblastic leukemia

Abstract: Background The outcome of approximately 20% of patients with acute lymphoblastic leukemia (ALL) remains poor because of disease recurrence. We examined whether DNA methylation of cadherin superfamily genes is a useful biomarker for ALL relapse. Procedure We used Infinium Methylation 450K Arrays to assess genome‐wide DNA methylation status. The methylation status of each individual gene was then determined by a combination of bisulfite restriction analysis and genome bisulfite sequencing. mRNA expression was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Moreover, a vast array of studies has identified individual PCDH downregulation due to promoter hypermethylation or somatic aberrations (see Table 2). The most frequently reported phenotypes resulting from loss of PCDH expression are increased proliferation and Costa et al, 2011;Lin et al, 2014a; Blood PH c GA12, GB7 Shi et al, 2007;Taylor et al, 2007nc 8, 10, 17 Ying et al, 2007Leshchenko et al, 2010;Narayan et al, 2011;Li et al, 2012b;Uyen et al, 2017 Brain PH c A8, A13, GC4, GA11 Waha et al, 2005;Abe et al, 2008; The clustered (c) and non-clustered (nc) PCDHs are grouped.…”
Section: Roles Of Pcdhs In Cancermentioning
confidence: 99%
“…Moreover, a vast array of studies has identified individual PCDH downregulation due to promoter hypermethylation or somatic aberrations (see Table 2). The most frequently reported phenotypes resulting from loss of PCDH expression are increased proliferation and Costa et al, 2011;Lin et al, 2014a; Blood PH c GA12, GB7 Shi et al, 2007;Taylor et al, 2007nc 8, 10, 17 Ying et al, 2007Leshchenko et al, 2010;Narayan et al, 2011;Li et al, 2012b;Uyen et al, 2017 Brain PH c A8, A13, GC4, GA11 Waha et al, 2005;Abe et al, 2008; The clustered (c) and non-clustered (nc) PCDHs are grouped.…”
Section: Roles Of Pcdhs In Cancermentioning
confidence: 99%
“…In addition, promoter methylation has been indicated to trigger inactivation of PCDH-17/20 in various types of cancer. Therefore, aberrant promoter methylation may be a competent diagnostic and prognostic biomarker for cancer ( 55 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypermethylation of promoters of a number of TSGs, such as EGF-containing fibulin extracellular matrix protein 1, glutathione S-transferase P1, suppressor of cytokine signaling 3, 3OST2, basic helix-loop-helix family member E22/cysteine deoxygenase 1/CUGBP Elva-like family member 4, SHP1 and transmembrane protein with EGF-like and two follistatin-like domains 2, have been studied in certain EC tissues and cell lines (such as Ishikawa and KLE) and the methylation frequency is high (26)(27)(28)(29)(30)(31). The present study investigated five TSGs (HOXD10, SHH, ZNF545, PCDH17 and MEIS1) whose promoters are reported to be hypermethylated in other malignancies but have not been evaluated for methylation in EC (32)(33)(34)(35)(36)(37)(38)(39)(40). For example, HOXD10 is hypermethylated and lowly expressed in colon adenocarcinoma cells, which downregulates the RHOC/AKT/MAPK pathway to enhance apoptosis and restrict the proliferation, migration and invasion of colon adenocarcinoma (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…ZNF545 functions as a tumor suppressor in colorectal cancer and is frequently inactivated by promoter methylation (36,37). Hypermethylation of PCDH17 is correlated to poor prognosis in acute lymphoblastic leukemia (38,39). MEIS1 genes are frequently hypermethylated in different types of leukemia (40).…”
Section: Introductionmentioning
confidence: 99%